The Juridical Analysis of Constitutional Court Decision No. 87/PUU-XXI/2023 on KPK - Sujono, Sujono; Rahmat, Diding; Permana, Sandhi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study analyzes Constitutional Court Decision Number 87/PUU-XXI/2023 concerning the authority of the Corruption Eradication Commission in coordinating and controlling the investigation, prosecution, and trial of concurrent jurisdiction corruption cases. The research employs normative legal methods with statute and historical approach. The findings indicate that the decision does not alter the justiciability of military courts in handling corruption cases committed exclusively by members of the Indonesian National Armed Forces as the non-concurrent jurisdiction. However, in corruption cases involving both civilian and military elements, the determination of the competent court whether from the general judiciary or military judiciary depends on the defined primary impact of the offense on public or military interests through joint assessment by the Military Prosecution Authority and the State Prosecutor. The legal implications of this decision affirm that the Corruption Eradication Commission retains its authority to handle connectivity corruption cases by adhering to the procedural law on concurrent jurisdiction as regulated in the Indonesian Criminal Procedure Code and Law No. 31 of 1997 on Military Judiciary. During the investigation phase, the Corruption Eradication Commission collaborates with a dedicated concurrent investigation team from the military judiciary comprising military prosecutors and military police. The examination of investigation results is conducted by the State Prosecutor of the Attorney General’s Office instead of the Commission’s prosecutors or the Military Prosecutor. If the case proceeds to trial at the Corruption Court, the prosecution is led by Commission prosecutors, whereas if it is tried in a military court, the prosecution is led by the Military Prosecutor.